Anestesia em Jacaré-americano (Alligator mississipiensis) para Amputação de Membro - Gorczak, Rochelle; Chaves, Rafael Oliveira; Teixeira, Marcella Linhares; de Freitas, Ítalo Barros; Martins, Raimy Costa; Valandro, Marilia Avila; Copat, Bruna; Soares, André Vasconcelos (Acta Scientiae Veterinariae, 2017)
Background: The knowledge of secure anesthetic protocols for reptiles is very important, especially because they are aggressive species and they have peculiar physiology, unpredictable reactions to the same drug in different environmental conditions and different physiological responses can be observed. The anesthetic protocol aims immobilization, analgesia and muscle relaxation for adequate, safe and easily reversible anesthesia. Few reports have been described on anesthesia in animals and, before that, the objective of this study is to report the anesthetic protocol that was used and vital parameters monitoring in an Alligator mississipiensis that was submitted to surgery for limb amputation. Case: A female American alligator was attended, with about 8-year-old, 2 m long and 268,964 pounds, with fight history with other animal six months ago, resulting in a wound in the right toracic limb. When the lesion occurred, it was the breeding season of the species, so we chose not to perform the treatment at that time. An X-ray of the member was performed, which showed, among other changes, osteomyelitis and septic arthritis. Thus, the limb amputation was indicated. Ketamine association (10 mg/kg) and medetomidine (0.1 mg/kg) were used as anestesic premedication, both administered intramuscularly. For anesthetic induction, propofol (4 mg/kg) intravenously was used. The animal was intubated using an endotracheal tube number 11 without inflating the cuffing, and for the maintenance it was employed isoflurane. The heart rate was measured using Doppler and the respiratory rate by visual and balloon observation in the oxygen circular system. The other parameters were measured using a multiparameter monitor sensor connected to the tongue. The local anesthetic block was made close to the incision line, the medium third humerus with 2 mg/kg of 2% lidocaine without vasoconstrictor, diluted in 0.9% NaCl until the volume of 10 mL is completed to assist in analgesia. The parameters recorded during the procedure, which lasted 80 min, remained within the normal pattern of species (three breaths per minute, 30 heart beats per min and 80.6°F temperature). After surgery meloxicam (0.2 mg/kg) and atipamezole reverser (0.5 mg/kg) were administered, both intramuscularly. The animal took about seven hours to fully return from anesthesia. Discussion: Different anesthetics protocols may be employed to crocodilians using both local anesthetic techniques and general, in order to promote analgesia, muscle relaxation and adequate anesthesia. Still, it is very important to monitor the patient during the procedure, in order to be a different physiology kind of species. Cardiac auscultation is quite difficult in these animals, so it is recommended to use non-invasive electronic equipment as the Doppler, the multiparameter monitor, the pulse oximeter and esophageal stethoscope for assistance in monitoring heart and respiratory rate, providing important trans-operative information. The realization of amputations in crocodilians is common, however there are few reports in the literature about their anesthesia, this way, this article has a significant contribution to a better anesthetic protocol clarification to be used in these animals. Therefore, it is concluded that the anesthetic protocol based on premedication with ketamine and medetomindina, propofol induction and maintenance with isoflurane, besides local anesthesia with lidocaine was effective and safe for thoracic limb amputation surgery in an American alligator.